Novel adsorbents based on eggshell functionalized with iron oxyhydroxide for phosphorus removal from liquid effluents. (August 2020) - Almeida, Patrícia V.; Santos, Andreia F.; Lopes, Daniela V.; Gando-Ferreira, Licínio M.; Quina, Margarida J.
Abstract: Phosphorus is an important and irreplaceable macronutrient for biological processes and is on the "list of Critical Raw Materials" of the European Union. Accumulation in water bodies requires an extra effort to promote its recovery. This study aims to synthesize, characterize and test a reliable adsorbent in acidic to neutral conditions. Several chemical modifications are tested to select the best adsorbent. Through the screening phase, it is possible to conclude that the chemical modification of calcined eggshell with magnesium and iron (III) does not improve the adsorption capacity. Thus, the material produced with 2/3 of iron and 1/3 of calcined eggshell reveals the best properties, OFeCES.0.5 (specific surface area of 270 m 2 /g) and performance to proceed with the tests. The influence of initial pH and adsorbent dosage is investigated to determine the best operating conditions. The adsorbent revealed better performance in acidic conditions (pH < 6) than in basic medium. Langmuir-Freundlich model reveals the best fitting (R 2 = 0.989), with a maximum adsorption capacity of 69.5 mg/g. The pseudo-first-order model describes the adsorption kinetic, with constants between 0.0353 and 0.0126 1/min, for an initial concentration of 50 and 400 mg P-PO4 /L. The adsorbent selected is regenerated with an efficiency of 50 % using an alkaline solution. In contact with a real effluent, the iron oxyhydroxide removes 50 % of phosphate. This work shows that iron oxyhydroxide with calcined eggshell has the potential as an adsorbent to remove phosphate from wastewaters.